Genetic diversity of six rice cultivars revealed by enzyme electrophoresis - Djoko T. Iskandar; Tjan Kiauw Nio; Asep Sosyandi (Zuriat, 1992)
Genetic diversity and similarity of six rice cultivars were analyzed by potato starch gel electrophoresis. Three local cultivars, 'Hawara Batu', 'Pandan Wangi', and 'Singkarak' were already homozygous for all 23 examined loci. Two cultivars have a rare allele, specific for each cultivar. White glutinous is the most polymorphic cultivar in having three segregating loci. Acp-193can be considered as a prove that crossing wich involved 'Sentani', and white glutinous rice has been performed in the past. This report also indicates that both upland cultivars are properly placed in the variety indica, and the three lowland rice are the variety japonica. The white glutinous rice is properly placed in the variety japonica based on four diagnostic loci.